Statistika Demografi Riptortus linearis F. (Hemiptera: Alydidae) pada Kacang Panjang (Vigna sinensis L.) - Amanda Mawan; Herma Amalia (Jurnal Entomologi Indonesia, 2011)
Riptortus linearis is one of the major pests on long bean. In order to control R. linearis, basic informations such as biology and life table are needed. The objective of this research is to study the life table of R. linearis on long bean under laboratory condition. This research was conducted from October 2009 to Februari 2010 at Laboratory Bioecology Parasitoid and Predator, Department of Plant Protection, Faculty of Agriculture, Bogor Agricultural University. The variables that were observed in this study consist of: 1) length of growing period from nymphs to imago, 2) adult life span, 3) fecundity, A life table was constructed using life table cohort type. The results showed that the egg stage lasted for 6:37 hours, while the second instar nymph stage I, II, III, IV,V, and VI takes place 2.06, 4.75, 4.55, 4.54, 6.2, and 6.67 days,consecutively. The life span of R. linearis is 29.3 days. The net reproductive rate (R0) R. linearis on long bean is 22.07 individual per female per generation, the innate capacity for increase (rm) 0.06 individual female per day, and the mean generation time (T) 49.94 days.